Geometry of Riemann surfaces : proceedings of the Anogia conference to celebrate the 65th birthday of William J. Harvey - Harvey, William J., 1941-; Gardiner, Frederick P.; González-Diez, Gabino; Kourouniotis, Christos (London Mathematical Society lecture note series, 2010)
Riemann surfaces is a thriving area of mathematics with applications to hyperbolic geometry, complex analysis, conformal dynamics, discrete groups, & algebraic curves. This collection of articles presents original research & expert surveys of related topics, making the field accessible to research workers, graduate students & teachers.